On the Study of Exciton Binding Energy with Direct Charge Generation in Photovoltaic Polymers. (20th September 2016) - Li, Ho‐Wa; Guan, Zhiqiang; Cheng, Yuanhang; Lui, Taili; Yang, Qingdan; Lee, Chun‐Sing; Chen, Song; Tsang, Sai‐Wing
Abstract : Overcoming the strong excitonic effect in organic photovoltaics (OPVs) is one of the key strategies for the design of materials and device structures. Approaches to measure the binding energy in organics are, however, not readily available. Here, the electrical and optical quantum efficiencies of a series of conjugated photovoltaic polymers are systematically studied. It is found that there is generally a secondary onset in external quantum efficiency (EQE) spectrum at high excitation energy, independent of optical absorbance of the materials. Combining photoluminescence quantum yield measurement and adding a small amount (1 wt%) of fullerene acceptor in polymer blends, it further confirms that the pristine polymer EQE spectrum has a transition from exciton to free‐charge generation with increased excitation energy. Strikingly, by comparing the reported photoemission spectroscopy results, the secondary onsets in the EQE spectra have excellent agreement with the transport gap ( E g ) in corresponding materials. Consequently, the exciton binding energies of the polymers can be obtained with the smallest 0.6 eV in PCE10 to the largest 1.2 eV in MEHPPV. The results of this study demonstrate a facile access to the transport gap and exciton binding energies in organic semiconductors. This provides valuable information for further understanding the strong excitonic effect in photovoltaic cells. Abstract : Primary photoexcitation processes in pristine photovoltaic polymers are investigated. It is found that free charges can be directly generated into delocalized states upon excitation. Such processes are strongly dependent on the exciton binding energy and corresponding electronic states. This sheds light on the understanding of charge dissociation process in organic photovoltaics.